Why the gaze behavior of expert physicians and novice medical students differ during a simulated medical interview: A mixed methods study. - Rie Yamada; Kuangzhe Xu; Satoshi Kondo; Makoto Fujimoto (PLoS ONE)
Human cognition is reflected in gaze behavior, which involves eye movements to fixate or shift focus between areas. In natural interactions, gaze behavior serves two functions: signal transmission and information gathering. While expert gaze as a tool for gathering information has been studied, its underlying cognitive processes remain insufficiently explored. This study investigated differences in gaze behavior and cognition between expert physicians and novice medical students during a simulated medical interview with a simulated patient, drawing implications for medical education. This study employed an exploratory sequential mixed methods design. During the simulated medical interview, participants' gaze behavior was measured across five areas: the patient's eyes, face, body trunk, medical chart, and medical questionnaire. A hierarchical Bayesian model analyzed differences in gaze behavior between expert physicians and novice medical students. Then, a semi-structured interview was conducted with participants to discern their perceptions during their gaze behavior; their recorded gaze behavior was presented to them, and analyzed using a qualitative descriptive approach. Model analyses indicated that experts looked at the simulated patient's eyes less frequently compared to novices during the simulated medical interview. Expert physicians stated that because of the potential for discomfort, looking at the patient's eyes was less frequent, despite its importance for obtaining diagnostic findings. Conversely, novice medical students did not provide narratives for obtaining such findings, but increased the number of times they did so to improve patient satisfaction. This association between different perceptions of gaze behavior may lead to new approaches in medical education. This study highlights the importance of understanding gaze behavior in the context of medical education and suggests that different motivations underlie the gaze behavior of expert physicians and novice medical students. Incorporating training in effective gaze behavior may improve the quality of patient care and medical students' learning outcomes.